Effect of metabolic syndrome on coronary artery atherosclerotic plaque in type 2 diabetes mellitus patients - Zhang, Yu-shan; Shi, Rui; Jiang, Yi-Ning; Gao, Yue; Wang, Jin; Li, Yuan; Yang, Zhi-Gang (Frontiers in Endocrinology, 2025)
BackgroundThe effect of MS on coronary artery plaques detected by coronary computed tomography angiography (CCTA) in type 2 diabetes mellitus (T2DM) patients is not fully understood. This study aimed to investigate the effect of MS and its components on coronary artery plaques by comparing CCTA characteristics, including plaque types, the severity of coronary plaques and high-risk plaques between T2DM patients with and without MS.MethodsThis study retrospectively enrolled 2,431 patients with T2DM who underwent Coronary Computed Tomography Angiography (CCTA) at West China Hospital between January 2015 to February 2022. These patients were divided into two groups based on the presence or absence of metabolic syndrome (MS). The plaque type, coronary artery stenosis, extent of coronary artery plaques, high-risk coronary plaque features, the segment involvement score (SIS), the segment stenosis score (SSS) and multivessel disease (MVD) based on CCTA data were evaluated and compared between two groups.ResultsFor T2DM patients, those with MS (61.5%, n=1496) had more noncalcified/mixed plaques, more nonobstructive stenosis and higher SIS and SSS values than those without (P < 0.05 for all). The proportion of patients with any noncalcified plaque, any mixed plaque, SIS≥4 and SSS≥7were in parallel with the numbers of MS components (P for trend<0.01 for all). Multivariate logistic regression revealed that MS were independently associated with any noncalcified plaque (OR=1.232, P =0.024), any mixed plaque (OR=1.307, P=0.006), any nonobstructive stenosis(OR=1.615, P = 0.001), SIS≥4 (OR=1.529; P<0.001), SSS≥7 (OR=1.387; P=0.001), and any spotty calcification (OR=1.870, P =0.001) in T2DM patients after adjusting for the confounding factors.ConclusionMS is independently associated with adverse coronary artery plaque characteristics in Type 2 Diabetes Mellitus (T2DM) patients, including increased mixed, noncalcified, nonobstructive, spotty calcification plaques, as well as extensive coronary artery disease (CAD). These findings highlight the need for early detection and management of MS to reduce cardiovascular risks in T2DM patients.